HEALTH COACHING SUCCESS TIPS : A LITERATURE REVIEW - Wahyudi, Chandra Tri; Nursasi, Astuti Yuni (Universitas Respati Yogyakarta, 2021)
Health coaching is a way of expanding the scope of health services through health promotion and disease prevention efforts by giving information in order to improve preventive behaviour in the community. The success of health coaching is determined by health workers’ understanding of the influencing factors. However, not many researches have been done in this area. Outlining evidence-based information within nursing field in regard to factors that determine the success of health coaching. This study is a non-systematic literature review analysing 10 related journals. The success of health coaching is determined by several factors including, agreement between both parties, good trainer (confidence, responsible, thorough, and appreciative), supportive trainer, motivated patients, collaboration between trainer and patients, good communication skills, frequency and duration of interaction between them. Several studies conducting telephone-based health coaching showed a significant success in converting patients’ behaviour into preventive behaviour. Keywords: Health Coaching; Health Promotion; Disease Prevention; Literature Review